2006
DOI: 10.1007/s11103-006-9025-y
|View full text |Cite
|
Sign up to set email alerts
|

EST database for early flower development in California poppy (Eschscholzia californica Cham., Papaveraceae) tags over 6000 genes from a basal eudicot

Abstract: The Floral Genome Project (FGP) selected California poppy (Eschscholzia californica Cham. ssp. Californica) to help identify new florally-expressed genes related to floral diversity in basal eudicots. A large, non-normalized cDNA library was constructed from premeiotic and meiotic floral buds and sequenced to generate a database of 9,079 high quality Expressed Sequence Tags (ESTs). These sequences clustered into 5,713 unigenes, including 1,414 contigs and 4,299 singletons. Homologs of genes regulating many asp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
40
0

Year Published

2007
2007
2015
2015

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 37 publications
(41 citation statements)
references
References 69 publications
1
40
0
Order By: Relevance
“…Further efforts with this plant have yielded a total of 25 000 ESTs from seedlings, stems, roots and elicitor-treated cell cultures (Ziegler et al, 2005(Ziegler et al, , 2006Zulak et al, 2007). A recent floral genome project contributed 11 000 ESTs from Eschscholzia californica (Carlson et al, 2006), and the release of a Coptis japonica database has also been reported Kato et al, 2007). NAPGEN (Natural Products Genomic Research), a consortium of Canadian investigators, has recently established a database of over 400 000 ESTs from a wide variety of plants that accumulate potentially health-related bioactive metabolites.…”
Section: Expressed Sequence Tagsmentioning
confidence: 99%
“…Further efforts with this plant have yielded a total of 25 000 ESTs from seedlings, stems, roots and elicitor-treated cell cultures (Ziegler et al, 2005(Ziegler et al, , 2006Zulak et al, 2007). A recent floral genome project contributed 11 000 ESTs from Eschscholzia californica (Carlson et al, 2006), and the release of a Coptis japonica database has also been reported Kato et al, 2007). NAPGEN (Natural Products Genomic Research), a consortium of Canadian investigators, has recently established a database of over 400 000 ESTs from a wide variety of plants that accumulate potentially health-related bioactive metabolites.…”
Section: Expressed Sequence Tagsmentioning
confidence: 99%
“…RNA was extracted from each of the three sets of buds separately, according to the manufacturer's protocol (http:// www.ambion.com/techlib/prot/bp_1911.pdf) for the RNAqueous®-Midi Kit (Ambion), with modifications as per Carlson et al (2006). RNA was precipitated using 0.1 volumes sodium acetate and three volumes of 100% ethanol.…”
Section: Rna Extractionmentioning
confidence: 99%
“…The amount of mRNA obtained was 32.9 μg, a yield of approximately 12.4 μg of mRNA per gram of bud tissues. cDNA library construction A directional cDNA library, designated Ltu01, was constructed from approximately 7 μg of mRNA using the ZAP-cDNA® Synthesis Kit (Stratagene), according to manufacturer's instructions (http://www.stratagene.com/ manuals/200401.pdf), and following the modifications of Carlson et al (2006). The pBluescript II SK(+/−) phagemid vector form of the library was excised from an aliquot of the lambda vector (into SOLR host cells) before library manipulation for DNA sequencing.…”
Section: Mrna Isolationmentioning
confidence: 99%
See 1 more Smart Citation
“…The vector, repetitive, chloroplast, and mitochondrial sequences were removed and the trimmed sequences were excluded from further analysis when they were less than 100 bp or they had greater than 4 % ambiguous bases (Carlson et al 2006;Masoudi-Nejad et al 2006). The remaining high quality ESTs of each library were subsequently clustered and assembled into unigenes (contigs and singletons) using EGassembler with Overlap percent identity cutoff >80 %.…”
Section: Sequence Processing Similarity Search and Annotationmentioning
confidence: 99%